2007
DOI: 10.1093/nar/gkm1045
|View full text |Cite
|
Sign up to set email alerts
|

Functional endogenous LINE-1 retrotransposons are expressed and mobilized in rat chloroleukemia cells

Abstract: LINE-1 (L1) is a highly successful autonomous non-LTR retrotransposon and a major force shaping mammalian genomes. Although there are about 600 000 L1 copies covering 23% of the rat genome, full-length rat L1s (L1Rn) with intact open reading frames (ORFs) representing functional master copies for retrotransposition have not been identified yet. In conjunction with studies to elucidate the role of L1 retrotransposons in tumorigenesis, we isolated and characterized 10 different cDNAs from transcribed full-length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 80 publications
3
42
0
Order By: Relevance
“…Like ORF2p, it shows a remarkable cis preference, that is, it associates preferentially with its encoding transcript (15,16). L1ORF1p can be localized in the cytoplasm (in putative stress granules) as well as in the nucleus (17,18) and can also be identified in large L1 ribonucleoprotein particles (RNPs) fractionated from cytoplasmic extracts (16,19,20).…”
mentioning
confidence: 99%
“…Like ORF2p, it shows a remarkable cis preference, that is, it associates preferentially with its encoding transcript (15,16). L1ORF1p can be localized in the cytoplasm (in putative stress granules) as well as in the nucleus (17,18) and can also be identified in large L1 ribonucleoprotein particles (RNPs) fractionated from cytoplasmic extracts (16,19,20).…”
mentioning
confidence: 99%
“…When CHL cells are allowed to grow undisturbed in a confined space, genomic long interspersed nuclear element (LINE) sequences are transcriptionally spontaneously activated at relatively low cellularity, later resulting in the retrotransposition of LINE sequences and population death. 8,9 These findings have been confirmed by Kirilyuk & Tolstonog et al, 10 who also identified a functional LINE retrotransposon from a pool of CHL cell cDNAs. They determined the activity of this retrotransposon in HeLa and CHL cells, demonstrating its mobilization in CHL cells.…”
Section: Introductionmentioning
confidence: 62%
“…[8][9][10] Mathematical modelling and growth curve analysis was inferred as described below. In an undisturbed culture in a confined space, CHL cell growth can be accurately simulated (correlation coefficient r = .9957)…”
Section: Growth Curve Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a functional L1 retrotransposon has been identified in rat chloroleukemia cells (Servomaa and Rytomaa 1990;Kirilyuk et al 2008). Furthermore, elements identified in silico might add to the list of potentially active ERVs (Baillie et al 2004;Gibbs et al 2004).…”
Section: à6mentioning
confidence: 99%